Synthesis and biological antimicrobial activity evaluation of furans from Lycopersicum against UPEC strains. (Eurasian Medical Research Periodical, 2022)
Medicinal plants are being traced and screened for novel therapeutics which could address many of the ailments including ever rising antibiotic resistance. Urinary tract infections are also common and is affecting a vast ratio of the human population adversely affecting the economical and health status of individuals. This prompted us to screen for novel antimicrobials which could inhibit the growth and motility of these pathogens. Lycopersicum (tomato) is said to be anticancerous and antibacterial. For the first time, we focused on purifying compounds from the fruit, and studying the antibacterial activity. Qualitative and quantitative analysis of purified compounds were performed by disc diffusion, MIC, motility assay and gene expression studies. We concluded from our studies that, the compounds could inhibit the bacterial growth and its swimming and swarming ability. Even the gene members responsible for flagellar and adhesion movements were also found to be down regulated on treating with the compounds.